1984
DOI: 10.1002/1097-0142(1984)54:4<675::aid-cncr2820540415>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Subacute and chronic myelomonocytic leukemia in children (juvenile CML). Clinical and hematologic observations, and identification of prognostic factors

Abstract: The clinical and hematologic characteristics of 38 children with subacute and chronic myelomonocytic leukemia (S & CMMOL) are described, and the prognostic significance of these characteristics as recorded at diagnosis is reported. The common and distinctive feature of these children was the excessive proliferation of cells of neutrophilic and monocytic series. The disease predominated in younger children, 95% were younger than 4 years, and boys were more affected than girls (22/16). The onset of the disease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
5

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(56 citation statements)
references
References 39 publications
2
49
0
5
Order By: Relevance
“…In other laboratory parameters, hypergammaglobulinemia can also be noted. 11 Karyotype analysis in JMML, by definition, must be negative for the Philadelphia chromosome t(9;22). There are no consistently recurring chromosomal translocations noted in JMML.…”
Section: Jmmlflaboratory Findingsmentioning
confidence: 97%
See 2 more Smart Citations
“…In other laboratory parameters, hypergammaglobulinemia can also be noted. 11 Karyotype analysis in JMML, by definition, must be negative for the Philadelphia chromosome t(9;22). There are no consistently recurring chromosomal translocations noted in JMML.…”
Section: Jmmlflaboratory Findingsmentioning
confidence: 97%
“…11,27 Owing to infiltration by relatively normal-appearing monocytes and macrophages into nonhematopoietic organs, JMML patients can also present with secretory diarrhea or bloody diarrhea, as well as pulmonary abnormalities or pulmonary failure, from frequent infiltration into the lungs and gastrointestinal tract. 28 Central nervous system involvement is quite rare.…”
Section: Jmmlfclinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…These children have most often been referred to as juvenile chronic myeloid leukemia (JCML) in the British and American literature, 7,8 whereas others have favored the FAB term CMML. 4,[9][10][11] An International Working Group concluded that the different terminology did not reflect the existence of different disorders and proposed the term juvenile myelomonocytic leukemia (JMML). The term has attained international acceptance 6,[12][13][14] and will be used throughout this paper.…”
Section: Introductionmentioning
confidence: 99%
“…All 3 de novo cases occurred in children age Ͻ than 2 years. The prognosis of MDS is somewhat better in very young children, 20 and Bader-Meunier et al recently reported spontaneous hematologic disease remissions in three children with Noonan syndrome-associated chronic myelomonocytic leukemia. 21 None of their patients had monosomy 7.…”
Section: Discussionmentioning
confidence: 99%